Forced Savings and Repressed Inflation in the Soviet Union : Some Empirical Results - Blejer, Mario (IMF Working Papers; Working Paper ;, 1991)
In countries such as the Soviet Union, where wealth is mainly stored in monetary assets, the behavior of the money to income ratio is a poor indicator of the growth of undesired monetary balances (monetary overhang). In those countries a monetary overhang is primarily a wealth overhang, which has to be analyzed by evaluating deviations of actual from desired wealth holdings; this requires an empirical analysis of consumption and saving decisions. In this paper, we present estimates of a consumption function for the Soviet Union, from which an evaluation of the monetary overhang existing at the end of 1990 is derived.